MODERASI BERAGAMA DALAM RUANG DIGITAL: GERAKAN OPINI DIGITAL #SKB3MENTERI - Nadya Amalia Nasution; Umi Rojiati (Tatar Pasundan : Jurnal Diklat Keagamaan, 2021)
The study examines Digital Movement of Opinion (DMO) by using hastag #SKB3Menteri hashtags on Twitter, thus forming a mobilization of digital opinion support between actors and hashtags as well as digital opinions. The research data was taken through Netlytic software ranging from February 03, 2021 to February 11, 2021. The method used is Social Network Analysis combined both quantitative and qualitative approach. Quantitatively, the study investigated 2500 samples from communication networks and tweets #SKB3Menteri as many as 3,232. Qualitatively, the researchers analyzed the text which describes social networks related to #SKB3Menteri. The results showed that #SKB3Menteri hashtag creates mobilization with a wide network system. The study also showed the hashtag was able to reach out Twitter users to giving their opinions.  Keywords: Religious moderation; Twitter; SKB 3 Ministers; Digital Movement of Opinion; Social Network Analysis